The Value of Thrombus Markers Applied in Patients with Respiratory Failure: Thrombus Markers in Respiratory Failure - Chen, Yingqun; Yin, Zihan; Wang, Junshi; Yan, Cunliang; Lin, Xuwei; Huang, Lei (Journal of Medical Biochemistry, 2024)
Background: This work assessed the value of novel thrombus markers—thrombin-antithrombin complex (TAT), plasmin-α2-plasmin inhibitor complex (PIC), thrombomodulin (TM), and tissue plasminogen activator-inhibitor complex (t-PAIC) applied in patients with respiratory failure (RF), including their role in predicting thrombus formation, evaluating prognosis, and assessing disease severity.Methods: eighty patients with RF were enrolled and categorized into mild (n = 10), moderate (n = 9), and severe (n = 71) groups based on disease severity. Meanwhile, patients were also classified into thrombus (n = 14) and non-thrombus (n = 76) groups based on the presence of thrombus. Furthermore, they were assigned into survival (n = 70) and death (n = 20) groups based on prognosis. Traditional coagulation indicators, thrombus markers, infection-related parameters, and respiratory-related indicators were compared among patients in different groups. This work explored the predictive effects of these indicators on the degree of respiratory failure, thrombus formation, and prognosis in various patient groups. Additionally, correlations of thrombus markers and traditional coagulation indicators to respiratory-related indicators and infection-related indicators were analyzed.Results: upon admission, levels of thrombin-antithrombin complex (TAT), plasmin-α2-plasmin inhibitor complex (PIC), and tissue plasminogen activator-inhibitor complex (t-PAIC) in the thrombus group were sharply higher in contrast to those in the non-thrombus group, showing obvious differences (P